Solve for s s/3-0.6=1.2

Math
s3-0.6=1.2
Move all terms not containing s to the right side of the equation.
Tap for more steps…
Add 0.6 to both sides of the equation.
s3=1.2+0.6
Add 1.2 and 0.6.
s3=1.8
s3=1.8
Multiply both sides of the equation by 3.
3⋅s3=3⋅1.8
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3⋅s3=3⋅1.8
Rewrite the expression.
s=3⋅1.8
s=3⋅1.8
Multiply 3 by 1.8.
s=5.4
s=5.4
Solve for s s/3-0.6=1.2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top